Analisis Rasio Kompresi AC Split R32 yang Diretrofit R290 di Ruang Akomodasi Kapal - Ulum, Rizka Noor Miftakhul; Sekti, Irsat Surya; Noviarianto, Noviarianto; Nugroho, Anang Budhi; Supardi, Supardi (Jurnal Maritim Polimarin, 2025)
Air conditioning (AC) systems play a crucial role in maintaining thermal comfort within ship accommodation spaces, especially during operations in tropical climates. However, the use of refrigerants such as R32 raises environmental concerns due to its relatively high Global Warming Potential (GWP). This study aims to analyze the impact of retrofitting 40% by mass of R290 into a 1-HP split AC system originally designed for R32, focusing on the resulting compression ratio and cooling performance. The experimental method involved varying the inlet air temperatures to the evaporator (23°C, 25°C, and 27°C) and condenser (30°C and 35°C). Suction and discharge pressures of the compressor were measured to calculate the compression ratio. The results showed that R32 yielded the highest compression ratio of 3.09 and the lowest at 2.87, while R290 produced a maximum of 2.86 and a minimum of 2.60. These differences reflect the influence of each refrigerant’s thermodynamic properties on compressor operation. R290 demonstrates potential as an environmentally friendly alternative for marine air conditioning systems, although technical adjustments are required to maintain optimal system performance.